Penegakan Hukum Pidana Tindak Pidana Korupsi Pemberian Fasilitas Kredit Pada Bank Negara Indonesia Cabang Tanjungkarang - Sitorus, Jono Parulian; Fardiansyah, Ahmad Irzal; Siswanto, Heni; Dewi, Erna; Sumarja, FX (VIVA THEMIS, 2025)
The banking sector poses a serious threat to the integrity of the financial system and national development. Corruption cases at Bank Negara Indonesia (BNI) Tanjungkarang Branch showed abuse of authority, document manipulation, fictitious credit granting, and collusion between bank officials and debtors which caused state financial losses. This research aims to analyse criminal law enforcement against corruption in the provision of credit facilities with a case study at BNI Tanjungkarang. The method used is normative legal research with statutory and theoretical approaches, and qualitative prescriptive analysis. The results showed that law enforcement officials have carried out the law enforcement process through the stages of investigation, investigation, prosecution, and examination in court. The handling of this case reflects the seriousness of law enforcement in eradicating corruption in the state financial sector. This study concludes that the effectiveness of law enforcement requires clarity of legislation, solid inter-agency coordination, increased capacity of law enforcement officials, and strengthening the internal control system in the banking environment to prevent the recurrence of similar corrupt practices